2018
DOI: 10.1007/s12020-018-1740-z
|View full text |Cite
|
Sign up to set email alerts
|

The co-activator-associated arginine methyltransferase 1 (CARM1) gene is overexpressed in type 2 diabetes

Abstract: Increased CARM1 expression in type 2 diabetes suggests that epigenetic mechanisms are altered in human diabetes. The impact of lifestyle and pharmacological treatment on regulation of this enzyme should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…PRMT4 is widely expressed in tissues throughout the body and overexpressed in human patients with cancers and T2DM. 14,15 In our study, increased PRMT4 expression was observed in the WAT of STZ-induced mice. However, PRMT4 expression varies among different tissues in STZinduced models of diabetes.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…PRMT4 is widely expressed in tissues throughout the body and overexpressed in human patients with cancers and T2DM. 14,15 In our study, increased PRMT4 expression was observed in the WAT of STZ-induced mice. However, PRMT4 expression varies among different tissues in STZinduced models of diabetes.…”
Section: Discussionsupporting
confidence: 61%
“…14 In patients with T2DM, PRMT4 is overexpressed in the white blood cells. 15 A previous study has shown that this enzyme is also overexpressed in retinal pigment epithelial cells of rats with T1DM, where it induces apoptosis in these cells. 16,17 PRMT4 regulates various cellular processes, such as DNA repair, transcriptional coactivation, mRNA splicing, and protein translocation.…”
Section: Introductionmentioning
confidence: 95%
“…Co-activator-associated arginine methyltransferase 1 (CARM1) is a coactivator of transcriptional activation and forms homodimers, which is necessary for catalytic activity (Chen et al 1999;Higashimoto et al, 2007). Recently, CARM1 was found to be increased in patients with diabetes (Porta et al, 2019). Additionally, CARM1 is elevated and participates in the regulation of high-glucose (HG) treated human retinal pigment epithelial cells (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to lysine modification, there is much less information regarding histone arginine methylation in diabetic complications, including wound healing. A few studies have shown that PRMTs are involved in insulin secretion in β-cells and some are overexpressed in diabetes (122)(123)(124). However, PRMTs can, not only methylate histones, but also non-histone proteins (121).…”
Section: Histone Modificationsmentioning
confidence: 99%